Factors that influence dairy farmers’ decisions to implement Johne’s Disease control practices: a systematic review - Morrison, Rosie; Rose, David Christian (Elsevier, 2023)
Johne’s Disease (JD) is an infectious ruminant disease that can cause economic loss for famers through reduced milk yields and infertility and has negative implications for animal welfare. JD is endemic in the dairy populations of many countries and there has been significant effort by governments and industry to try and control it. However, these efforts have had limited success. Many studies look at individual control programmes or the adoption of Johne’s control measures; however a wider perspective on what drives farmer participation Johne’s control does not currently exist. This study seeks to fill this gap by conducting a systematic review informed by the PRISMA statement. The results suggest that psychological factors such as participation fatigue, cognitive dissidence over animal welfare and not having first-hand experience of the disease act as barriers to Johne’s control. To better promote Johne’s control, this review emphasises that control programmes need to engage farmers, advisers, and supply chain actors in their design and delivery of control programmes to account for differing attitudes and levels of knowledge.
Keywords: Behaviour change; Control; Disease; Eradication; Johne's